2015
DOI: 10.1242/jeb.122739
|View full text |Cite
|
Sign up to set email alerts
|

Host manipulation by an ichneumonid spider ectoparasitoid that takes advantage of preprogrammed web-building behaviour for its cocoon protection

Abstract: Host manipulation by parasites and parasitoids is a fascinating phenomenon within evolutionary ecology, representing an example of extended phenotypes. To elucidate the mechanism of host manipulation, revealing the origin and function of the invoked actions is essential. Our study focused on the ichneumonid spider ectoparasitoid Reclinervellus nielseni, which turns its host spider (Cyclosa argenteoalba) into a drugged navvy, to modify the web structure into a more persistent cocoon web so that the wasp can pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
1
26
0
1
Order By: Relevance
“…Some of them were collected as penultimate subadult females, and were kept until they made their final moult. Other adults were collected on their moulting webs, which were characterized by their small size, reduced number of radii, lack of spiral threads and presence of fibrous decorations [13], indicating that the spiders had just moulted to adults. They were convincingly assumed to be virgins, because preliminary observations had revealed that no female mates with a male when on a moulting web.…”
Section: Methodsmentioning
confidence: 99%
“…Some of them were collected as penultimate subadult females, and were kept until they made their final moult. Other adults were collected on their moulting webs, which were characterized by their small size, reduced number of radii, lack of spiral threads and presence of fibrous decorations [13], indicating that the spiders had just moulted to adults. They were convincingly assumed to be virgins, because preliminary observations had revealed that no female mates with a male when on a moulting web.…”
Section: Methodsmentioning
confidence: 99%
“…The same pattern was observed in C . argenteoalba [18] manipulated by Reclinervellus nielseni (Roman, 1923). In this study, a detailed comparison of web structures, building behavior, and silk spectral/tensile also showed that the few radii of both web types were decorated by many fibrous ultra violet-reflective threads.…”
Section: Discussionmentioning
confidence: 99%
“…The wasps lay one egg on the spider's abdomen, where the ectoparasitic larva develops by sucking the host’s hemolymph through perforated holes in the spider’s cuticle. Usually, the host spider builds a modified web just before the wasp larva enters the final stage of development [9–18], but, in some cases, the number of radii and spirals of the orb web gradually decrease over several days before the spider dies [19,20]. After the spider builds this modified structure, the larva kills its host, and builds its cocoon attached to the silk threads spun by the host.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations